PROSPECTS FOR THE USE OF ANTISEPTIC AGENTS IN THE PREVENTION OF SILKWORM DISEASES REARED UNDER THE CONDITIONS OF KARAKALPAKSTAN - CH. I. Bekkamov; U. A. Ospanova; M. A. Safarova; Sh. I. Ibrohimov (Modern American Journals, 2025)
Considering that antiseptic agents and their prepared concentrations have demonstrated effective results in the prevention and prophylactic treatment of infectious diseases in animals and insects, it is proposed to apply highly efficient antiseptics—such as hydrogen peroxide, alcohol, formalin, and ayran—under the conditions of Karakalpakstan for silkworms reared on mulberry. Their use is expected to prevent adverse effects on the biological indicators of silkworms, the duration of larval development, and the productivity and quality of the produced cocoons. Therefore, the application of these antiseptic preparations is recommended as a prospective and improved scientific approach for further research and practical implementation in sericulture.
Keywords: Sericulture, silkworm eggs, hybrid, incubation, larva, silkworm rearing house, sanitation and hygiene, silkworm rearing, animals, insects, subtropical, pathogenic microorganisms, bacterial, viral, fungal, lower unicellular, molecular, pathogenic, immunity, infectious diseases, laboratory, antibiotic, drug, antiseptic agent, preventive treatment, mulberry leaf, farming enterprises, cluster, silkworm-rearing unit, biological indicators, cocoon yield, quality.